Efektivitas Pembelajaran Daring Masa Pandemi Covid-19 pada Guru SD Kelas V Kecamatan Negara Tahun Ajaran 2021-2022 - Dewi, Made Sri Astika; Sudewiputri, Made Padmarani (Indonesian Research Journal on Education, 2022)
This study aims to know effectiveness the online learning process, the supporting factors and theinhibiting factors for teachers in carrying out online learning during the COVID-19 pandemic. This research was carried out at the fifth grade elementary school teacher in Negara District in the 2021/2022 academic year. This research uses a qualitative descriptive research method. The subjects used in this study were elementary school teachers in Class V in Negara District. Data collection techniques used in this study were open questionnaires, semi-structured interviews, documentation and field notes. The results and discussion of this study are that online learning is considered less effective for teachers, especially for elementary school age children, because learning is carried out online, the teacher alsodoes not feel optimal in providing learning materials so that the material is incomplete and the use of learning media in online learning is also felt to be inadequate maximum.